Implementation of Education in Business Practice Courses for Management and Accounting Major Studies - Mawardi Mawardi; Owen De Pinto Simanjuntak; Abdurohim Abdurohim; Rizka Elvira P; Akbar Akbar (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze implementation of education in business practice courses for management and accounting major students. This type of research is qualitative research. Informants in the study are students who took business practice courses and opened a business, each of which consisted of 5 students majoring in management and 5 students majoring in accounting at Private Higher Education in Medan City. This study uses qualitative data analysis. Based on research results conducted on 5 students majoring in management and 5 students majoring in accounting at Private Higher Education in Medan City who are made as informants, it resulted that 9 out of 10 informants are motivated from business practice courses, and there is 1 informant who stated that he is not motivated from business practice courses.